ChemInform Abstract: C—N Bond Formation via Cu‐Catalyzed Cross‐Coupling with Boronic Acids Leading to Methyl Carbazole‐3‐carboxylate: Synthesis of Carbazole Alkaloids. Issue 38 (10th September 2014) - Rasheed, Sk.; Rao, D. Nageswar; Reddy, K. Ranjith; Aravinda, S.; Vishwakarma, Ram A.; Das, Parthasarathi
Abstract Copper catalyzed N‐arylation of iodoarenes with boronic acids followed by palladium catalyzed intramolecular C‐H arylation provides carbazole‐3‐carboxylates including the naturally occurring alkaloids Clausine C (IVg), H (IVf) and L (IVe).